STRUCTURAL GENETIC RELATION OF MIGRATION PATHS AND HYDROCARBONS ACCUMULATION WITH EARTH CRUST MAGNETIC HETEROGENEITY OF NORTH-WESTERN PART OF THE DNIEPER-DONETS AULAKOGEN - Drukarenko, V.; Orlyuk, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Joint analysis of the magnetic heterogeneity and fault-block tectonics of the earth's crust is one of the methods for predicting migration routes and places for the accumulation of hydrocarbons. Investigations of the magnetic susceptibility of rocks revealed sufficiently high capabilities of the method for solving a wide range of problems: interpreting local magnetic anomalies over hydrocarbon deposits, dismembering and studying lithology of sedimentary sections, isolating and marking the area of reference magnetic horizons, and estimating the degree of oxidation-reduction processes. The deep-magnetic aspect of the oil and gas potential of the earth's crust is caused by the formation or transformation of ironcontaining minerals into magnetic varieties (mainly magnetite, native iron and pyrrhotite) in the zones of deep faults with the influence of reducing fluids. The enhancement or decrement of the magnetic susceptibility of rocks with the influence of hydrocarbons in sedimentary cover depends on the composition of iron compounds. Their formation is controlled by geochemical and thermobaric conditions. All iron oxides are reduced to magnetite (ferromagnetic mineral), and sulfides are reduced to pyrite (paramagnetic). The laboratory studies of the hydrocarbons influence on magnetic susceptibility of rock samples with the temperature from 3 bore-holes and mineralogical studies to identify magnetic minerals were performed. The rocks are presented by argillites, sandstones, aleurolites, limestone and concretion. Magnetic susceptibility changes were detected, χ of the most saturated and unsaturated rocks increased. The mineralogical composition of limestone (marl) was studied using a scanning electron microscope, the REMMA-202M. It was not possible to detect the iron-containing mineral, probably, due to the low resolution of the device, since, for example, pyrrhotite may be in a finely dispersed state. Magnetic susceptibility enhancement of the rocks can be explained either by the transitions of the pyrrhotite phase during heating process or, supposedly, by the presence of the maghemite phase and its transition to hematite. The experimental data of the density and magnetic susceptibility of the rocks obtained by the authors from 8 super deep bore-holes were analyzed. Samples present sedimentary cover and the Precambrian basement of the investigated region. Beside sedimentary rocks, there are also basalts, concretions, gneisses and granite gneisses. Magnetic susceptibility and density of the rocks vary widely. Rocks interval of reduced densities and increased magnetic susceptibility were found in a number of bore-holes as well as areas of argillites decompression deeper than 5000 m. Due to affiliation of these areas to local and deep faults and nodes of their intersection they can be considered as perspective for deep hydrocarbons.
Keywords: magnetic susceptibility; Dnieper-Donets aulacogen; oil and gas content; hydrocarbons